Growth and cranial development in the Andean frogs of the genus Telmatobius (Anura: Telmatobiidae): Exploring the relation of heterochrony and skeletal diversity - Barrionuevo, Jose Sebastian (2018)
Andean frogs of the genus Telmatobius occur at high elevations, they have an aquatic mode of life and large tadpoles. There are more than 60 species that closely resemble one another and have low values of genetic divergence. However, the skeleton, particularly the cranium, is interspecifically variable with respect to the different levels of development of some elements. Heterochrony is considered to have played a prominent role in generating phenotypic variation, especially among closely related species. Herein, the developmental origins of the adult cranial configuration of two species of Telmatobius are explored. The interactions among larval and postmetamorphic growth, sexual maturation, and ossification sequence in T. oxycephalus and T. rubigo are studied. Although there are no substantial changes in the sequences of ossification of the cranium, it is likely that differential timing of larval periods is related to adult cranial characters. The prolonged larval development of T. rubigo may result in peramorphic configurations of bones that ossify during pre-metamorphosis. This long developmental time would also explain why the gonads of T. rubigo are highly differentiated by the end of metamorphosis. In this species, sexual maturation may be attained precociously in relation to metamorphosis, thereby reducing postmetamorphic developmental time of late-onset bones, which have paedomorphic configurations (e.g., vomer, neopalatine, and columella). An inverse pattern characterizes T. oxycephalus, suggesting that the duration of larval life is related to skeletal configuration in Telmatobius.